Increased numbers of 6-sulfo LacNAc (slan) dendritic cells in hand transplant recipients - Baran, Wojciech; Koziol, Maria; Woźniak, Zdzisław; Banasik, Mirosław; Boratyńska, Maria; Kunze, Anja; Schäkel, Knut (Annals of transplantation, 2015)
BACKGROUND: Vascularized composite allotransplantation (VCA) is a modern option for the treatment of functionally significant limb and tissue defects. In our study we aimed to characterize the morphological and histological features of the hand transplant recipient skin rejection. - MATERIAL AND METHODS: We clinically evaluated the skin and mucous membranes and microscopically assessed biopsies taken from the patient's own skin and from the allogenic grafted limb (n=5). We also performed immunohistochemistry for presence of T lymphocytes (CD3, CD4, and CD8), B lymphocytes (CD20), macrophages (CD68), Langerhans cells (CD1a+), plasmacytoid dendritic cells (pDCs) (CD123+) and 6-sulfo LacNAc+ dendritic cells (slanDCs) (DD2+). - RESULTS: Only scattered pDCs were present in both own and skin grafts. The number of LC in the epidermis was higher in graft skin in all cases and CD1a+ cells were also present in the dermis in transplanted skin in patients with grade 1 rejection. Most interestingly, we identified far increased numbers of dermal slanDCs in the grafted skin. SlanDCs have a high capacity to produce proinflammatory cytokines and have been described as inflammatory dermal dendritic cells in psoriasis and lupus erythematosus. - CONCLUSIONS: It may be hypothesized that slanDCs identified in the skin after limb transplantation may support the local inflammatory skin reaction.